Making work pay: Wage insurance for the working poor - Barry Bluestone; Teresa Ghilarducci (Levy Economics Institute of Bard College, 1996)
Barry Bluestone of the University of Massachusetts and Teresa Ghilarducci of the University of Notre Dame show that although the poverty rate for elderly Americans has declined over the past three decades, the total number of persons in poverty has grown and the number of poor nonelderly adults in poverty has nearly doubled since 1970. The authors argue for a comprehensive and coherent strategy aimed at the working poor and those susceptible to highly fluctuating incomes. Two essential components of a wage insurance system already exist in the earned income tax credit (EITC) and the minimum wage. Neither by itself is an ideal solution to the wage poverty problem, but the two programs complement one another. What makes the two fit together so well is that the existence of a higher minimum wage actually reduces the negative productivity, fiscal impact, and moral hazard effects of the EITC, while the EITC makes up for the weak target efficiency and income adequacy of the minimum wage.
Keywords: 330